Once more from the top : a novel - Layden, Emily, 1989- (Mariner Books, 2024)
At the height of her career, legendary pop star Dylan Read, when her childhood best friend's body is found, is forced to reckon with the secret she's kept hidden for fifteen years, in this gripping and keenly observant novel about friendship, ambition and the cost of fame.